Good times, bad times: Innovation and survival over the business cycle - Elena Cefis; Orietta Marsili (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
High-potential new ventures are a source of economic growth, which policy makers call upon in times of crisis when entrepreneurship is seen as a remedy to economic downturn. Yet at these times new ventures face intensified selection, and survival hinges on heterogeneous capabilities. We examine how the innovative capabilities of new firms created in the Netherlands in 2001-2006, affected their survival likelihood before, during and after the 2007-2008 global financial crisis. We estimate a piecewise exponential model linking survival times, observed in the time period from 2001 to 2015, to longitudinal innovation data from the CIS. Our results show that new ventures innovating within two years from founding benefit of a long-term adaptive survival premium during and after the crisis. This premium and its duration over the stages of the crisis are contingent to the form of innovation: technological innovations entail a more effective and enduring premium, as compared to managerial innovations, which can be even detrimental for survival. Our study has implications for entrepreneurial management, by highlighting how the development of innovative capabilities at founding, lays the foundations for organisational adaptation and resilience in the longer term. Furthermore, our results can inform a policy approach that aims at sheltering from the storm of a financial crisis, those new ventures that do possess the specific and necessary adaptive capabilities, but that are also vulnerable because of the liabilities of newness and smallness. Such an approach could help to maintain alive the process of entrepreneurial experimentation during the crisis, and to boost economic recovery, without dispersing precious resources.
Keywords: L11; L25; D21; O32; 330; firm survival; environmental jolts; financial crisis; organisational adaptation; technological and non-technological innovation